Practice staff who refuse to have the Covid-19 vaccine. (2nd March 2021) - Mackenzie, Peter; Simsek, Ceylan
Abstract : There will always be people who refuse vaccinations for a variety of reasons. Dr Peter Mackenzie, Quality Assurance Lead and Ceylan Simsek, Case Management Assistant at Medical Protection, offer some guidance for practice managers